An Analysis of Directive Speech Act Found in “Moana 2” Movie - Gede Eka Suasta Putra; Ida Ayu Putri Gita Ardiantari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to analyze directive speech acts found in the animated movie Moana 2 using Searle’s (1979) theory of illocutionary acts. Directive speech acts are utterances that are intended to persuade the listener to take action, either directly or indirectly. The data were gathered through observation, by observing the film and reading the official script. According to the categories of directed speech acts, the utterances were categorized and interpreted using a descriptive qualitative technique. The result of data analyis showed that every character in the movie utilized a total of 45 directed speech acts. They were divided into five categories: warnings, suggestions, requests, commands, and advice. Command represented 40% of the data, making it the most dominant category among them. Requests and suggestions were following. This dominance highlights Moana’s strong leadership role, as she regularly employs commanding words to influence people and steer the plot. Additionally, the results showed how the social context, character relationships, and narrative suspense of the film all influence the directed speech actions. In this study, the role of directive acts in animated film was analyzed in detail, which advances the subject of pragmatics. It should offer helpful references for future studies on media language usage and speech act theory.